Penyesuaian Diri Mahasiswa Perantau di Universitas Aisyah Pringsewu Tahun 2023 - Shinta Okta Via Ningrum; Fixi Intansari (Jurnal Psikologi, 2023)
Adaptation is a process in life that involves mental and behavioral reactions when facing pressure, tension, frustration, conflicts, and life challenges, enabling individuals to adjust to new environments. The purpose of this research is to understand how out-of-town students adapt to their new environment outside Lampung. The informants in this study are three out-of-town students. The research employs purposive sampling as the sampling method. Data collection methods include semi-structured interviews, observation, and documentation. The data analysis technique used is interpretative phenomenological analysis (IPA). The results of this study indicate that the three informants when they were abroad had some difficulties in adjusting themselves and in the adjustments made by overseas students there were characteristics and factors that influenced adjustment.